A co‐formulation of pramlintide and insulin A21G (ADO09) improves postprandial glucose and short‐term control of mean glucose, time in range, and body weight versus insulin aspart in adults with type 1 diabetes. Issue 5 (31st January 2023) - Andersen, Grit; Eloy, Rosy; Famulla, Susanne; Heise, Tim; Meiffren, Grégory; Seroussi, Cyril; Gaudier, Martin; Mégret, Claire; Chan, You‐Ping; Soula, Olivier; Riddle, Matthew
Abstract: Aim: Pramlintide improves postprandial glucose but requires additional injections. We investigated the pharmacokinetics/pharmacodynamics, efficacy and safety of ADO09, pramlintide/insulin A21G co‐formulation, in type 1 diabetes (T1D). Materials and Methods: This double‐blinded, randomized, two‐period cross‐over study compared prandial administration of ADO09 or insulin aspart over 24 days in T1D using either ≤40 U bolus insulin per day [low‐dose group (LD), n = 28] or 40‐75 U [high‐dose group (HD), n = 16]. Glycaemic responses through continuous glucose monitoring, and pharmacokinetics/pharmacodynamics profiles following mixed‐meal‐tolerance tests were evaluated at baseline and at the end of treatment. Results: Glucose increments from 0 to 4 h after mixed‐meal‐tolerance test (primary endpoint) were 39% (not statistically significantly) lower with ADO09 in the low‐dose group and 69% lower in the high‐dose group. Mean continuous glucose monitoring glucose during ambulatory treatment was lower with ADO09 than with aspart (LD: –8.2 ± 7.9 mg/dl, p  = .0001; HD: –7.0 ± 10 mg/ml, p  = .0127), and time‐in‐range (70–180 mg/dl) improved (LD: +4%, p  = .0134; HD: +4%, p  = .0432). Body weight declined significantly with ADO09 (LD: –0.8 kg; HD: –1.6 kg). Hypoglycaemic events were slightly more frequent with ADO09 versus aspart (LD: 142 vs. 115; HD: 96 vs. 79). Gastrointestinal events occurred more frequently with ADO09 but were generally transient, and no other safety signals were identified. Conclusions: In comparison with aspart, ADO09 was well tolerated and effective in T1D across a wide range of dosage, significantly improving the average blood glucose level and body weight during 24 days of ambulatory treatment. Meal test profiles confirmed improvement of glycaemic patterns and other responses with ADO09.